The Effect of Service Quality, Trust, Hospital Image and Facilities on Patient Satisfaction in Outpatient Pharmacy Services - Jaka Arifin Budiyana; Istiatin Istiatin; Oong Ridhoi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research aims to test and analyze the influence of service quality, trust, hospital image and facilities on patient satisfaction in outpatient pharmacy services at Dr. RM. Soedjarwadi Mental Hospital. The research method used is quantitative. The number of samples used was 100 respondents with instrument testing in the form of validity and reliability tests. Furthermore, the research data was analyzed using Multiple Linear Regression, F-Test, t-test, and Coefficient of Determination. The results of the study indicate that cumulatively there is a significant influence between service quality, trust, hospital image, and facilities on patient satisfaction. Meanwhile, partially, of the four independent variables studied, three independent variables have a positive influence on patient satisfaction, namely trust, hospital image, and facilities. While one independent variable that does not have a significant influence on patient satisfaction is service quality.